Can two-dimensional confinement trigger the fragile-to-strong crossover in phase-change supercooled liquids. (February 2021) - Zhang, Qian; Chen, Yimin; Leng, Wenhao; Gu, Jierong; Mao, Yuanen; Shen, Xiang; Wang, Rongping; Xu, Tiefeng; Wang, Jun-Qiang; Wang, Guoxiang
Abstract: Recent fragile-to-strong crossover (FSC) concept in the crystallization kinetics study of phase-change supercooled liquids (PCLs) is attractive for screening the high-performance phase-change materials. It is important to search the FSC behavior in confined PCLs, like the two-dimensional confined PCLs, which is believed has fast crystallization and good thermal stability. Together with the ultrafast differential scanning calorimetry measurement and the generalized Mauro-Yue-Ellison-Gupta-Allan viscosity model, we here studied the crystallization kinetics of two-dimensional confined GeTe PCLs. It was found such confined PCLs has distinct FSC with large crossover magnitude is 2, confirming two-dimensional confinement can trigger the FSC behavior in PCLs. Graphical Abstract: The distinct fragile-to-strong crossover can be found in confined GeTe phase-change supercooled liquids with a two-dimension confined structure of [GeTe(7nm)/W(6nm)]20 . Image, graphical abstract